Inhibition of histone acetyltransferase GCN5 extends lifespan in both yeast and human cell lines - Huang, Boyue (Aging Cell, 2020)
Histone acetyltransferases (HATs) are important enzymes that transfer acetyl groups onto histones and thereby regulate both gene expression and chromosomal structures. Previous work has shown that the activation of sirtuins, which are histone deacetylases, can extend lifespan. This suggests that inhibiting HATs may have a similar beneficial effect. In the present study, we utilized a range of HAT inhibitors or heterozygous Gcn5 and Ngg1 mutants to demonstrate marked yeast life extension. In human cell lines, HAT inhibitors and selective RNAi‐mediated Gcn5 or Ngg1 knockdown reduced the levels of aging markers and promoted proliferation in senescent cells. Furthermore, this observed lifespan extension was associated with the acetylation of histone H3 rather than that of H4. Specifically, it was dependent upon H3K9Ac and H3K18Ac modifications. We also found that the ability of caloric restriction to prolong lifespan is Gcn5‐, Ngg1‐, H3K9‐, and H3K18‐dependent. Transcriptome analysis revealed that these changes were similar to those associated with heat shock and were inversely correlated with the gene expression profiles of aged yeast and aged worms. Through a bioinformatic analysis, we also found that HAT inhibition activated subtelomeric genes in human cell lines. Together, our results suggest that inhibiting the HAT Gcn5 may be an effective means of increasing longevity.